2021
DOI: 10.1177/1942602x211056371
|View full text |Cite
|
Sign up to set email alerts
|

The Huddle: A Daily Dose of Communication

Abstract: Teamwork and communication are critical to ensure safe and quality care for students. A huddle offers the team a daily dedicated time to connect with each other. Huddles are short, regular debriefings designed to engage clinical staff in discussions about existing or emerging safety issues. The huddle was already systematically and uniformly part of the daily practice at Akron Children’s Hospital’s School Health Services daily schedule prior to COVID-19. The pandemic increased the need for the daily huddle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…11,12 It differs from team meetings in the manner that it is a brief daily discussion, focusing on the plan of action for the day ahead. 13,14 Daily huddles can promote optimal patient outcome. 2,[14][15][16] It is the huddle leader's responsibility to keep huddles short, focused and task-oriented, making sure every topic is discussed.…”
mentioning
confidence: 99%
“…11,12 It differs from team meetings in the manner that it is a brief daily discussion, focusing on the plan of action for the day ahead. 13,14 Daily huddles can promote optimal patient outcome. 2,[14][15][16] It is the huddle leader's responsibility to keep huddles short, focused and task-oriented, making sure every topic is discussed.…”
mentioning
confidence: 99%
“…According to a recently published QI report, daily huddles have been shown to enhance communication among healthcare providers and patient safety responsiveness in an intensive care unit 5. Another similar study, from a hospital where daily huddles were a part of the routine for the last decade, showed that this practice helped them tide the pandemic with ease and bridge gaps in patient care 6…”
mentioning
confidence: 99%